Chrysin attenuates liver fibrosis and hepatic stellate cell activation through TGF-β/Smad signaling pathway. (5th October 2015) - Balta, Cornel; Herman, Hildegard; Boldura, Oana Maria; Gasca, Ionela; Rosu, Marcel; Ardelean, Aurel; Hermenean, Anca
Abstract: We investigated the protective effect of chrysin on chronic liver fibrosis in mice and the potential mechanism underlying TGF-β1-mediated hepatic stellate cells (HSCs) activation on fibrogenesis. Experimental fibrosis was established by intraperitoneal injection of mice with 20% v/v, 2 ml/kg CCl4 twice a week, for 7 weeks. Mice were orally treated with 3 doses of chrysin (50, 100 and 200 mg/kg) or with vehicle as control. For the assessment of the spontaneous reversion of fibrosis, CCl4 treated animals were investigated after two weeks of recovery time. Silymarin was used as standard hepatoprotective flavonoid. Histopathological investigations showed that hepatic fibrosis grade was markedly reduced in the chrysin groups compared to the fibrotic one. Moreover, CCl4 activated HSCs induced an upregulation of smooth muscle actin (α-SMA), an increased number of TGF-β1 immunopositive cells and marked up-regulation of TGF-β1. α-SMA and TGF-β1 levels were significantly reduced in all chrysin treated groups in a dose-dependent manner, whereas the level of spontaneous reversal of fibrosis was lower compared to all flavonoid treated groups. Liver mRNA levels of Smad 2 in the 50, 100 and 200 mg/kg chrysin treated groups were significantly reduced by about 88.54%, 92.15% and 95.56% of the corresponding levels in the fibrosis mice group. The results were similar for mRNA levels of Smad 3. The protective response to silymarin was almost similar to that seen with the highest doses of chrysin. In this study, we have shown that chrysin has the efficacy to reverse CCl4 -stimulated liver fibrosis by inhibition of HSCs activation and proliferation through TGF-β1/Smad pathway. These results suggest that chrysin may be useful in stopping or reversing the progression of liver fibrosis and might offer the possibility to develop a new therapeutic drug, useful in treatment of chronic liver diseases. Highlights: Effect of chrysin on CCl4 -induced liver fibrosis is studied. Chrysin inhibited liver fibrosis and TGF-β1-induced HSC activation. Chrysin blocked the TGF-β1/Smad signaling pathway. Chrysin administration restores normal hepatic architecture in fibrotic rats.